Evolution of three-point field goals shooting trends in EuroLeague basketball - Foteinakis, P. F.; Pavlidou, S. P. (Trends in Sport Sciences, 2024)
Introduction: Sports analytics in basketball plays a crucial role in devising innovative game strategies, enhancing scoring opportunities, and achieving greater success. A role of a threepoint shot in the EuroLeague basketball has been greatly influenced by analytics, evolving from a sporadically used tool to a fundamental aspect of basketball strategy.